Performa Ayam Broiler Strain Cobb yang Diberi Herbal Kunyit - Fitriana Akhsan; Harifuddin Harifuddin; Muh Irwan (Universitas Boyolali, 2020)
This research discusses about broiler chickens which are given turmeric herbs by giving through feed and drinking water. The chickens used were 96 Cobb DOC strains, 8 for each experimental unit. The study used 3 treatment and 4 repeat. The treatment is: T0 = basal feed, T1 = basal feed + 2% turmeric from the amount of feed consumption and T2 = basal feed + 2% turmeric from the amount of drinking water consumption. The parameters discussed in this study are the performance of broilers consisting of feed consumption, drinking water consumption, body weight gain, final body weight, feed conversion, mortality and income over feed and chicken costs. Feed consumption, drinking water consumption, body weight gain, final body weight, feed conversion and mortality are not supported by significant maintenance (P> 0.05). The highest income from feed and chicken costs in T2 training is Rp. 11,582. The conclusion of this research is the application of turmeric is more optimal if applied through drinking water at a level of 2%.